2016
DOI: 10.1080/14786419.2016.1222383
|View full text |Cite
|
Sign up to set email alerts
|

Composition of the essential oils of three Uzbek Scutellaria species (Lamiaceae) and their antioxidant activities

Abstract: The chemical composition of the essential oils obtained from aerial parts of Scutellaria immaculata Nevski ex Juz., Scutellaria ramosissima M. Pop. and Scutellaria schachristanica Juz. (Lamiaceae) growing wild in Uzbekistan was analysed by GC and GC-MS. The main constituents of the essential oils from S. immaculata were acetophenone (30.39%), eugenol (20.61%), thymol (10.04%) and linalool (6.92%), whereas constituents of the essential oils fromS. schachristanica were acetophenone (34.74%), linalool (26.98%) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 17 publications
5
18
0
Order By: Relevance
“…The IC50 value for the ABTS radical scavenging activity of the essential oil was 0.55 mg/mL, while those of the standards could not be determined precisely as they were lower than the lowest concentration tested. This result here is similar to the work by Mamadalievaa et al [17] who found that three Uzbek Scutellaria species also exhibited weak ABTS radical scavenging activity. The nitric oxide radical scavenging activities of the essential oil and the reference compounds are presented in Figure 4.…”
Section: Appl Sci 2016 6 439 7 Of 14supporting
confidence: 82%
“…The IC50 value for the ABTS radical scavenging activity of the essential oil was 0.55 mg/mL, while those of the standards could not be determined precisely as they were lower than the lowest concentration tested. This result here is similar to the work by Mamadalievaa et al [17] who found that three Uzbek Scutellaria species also exhibited weak ABTS radical scavenging activity. The nitric oxide radical scavenging activities of the essential oil and the reference compounds are presented in Figure 4.…”
Section: Appl Sci 2016 6 439 7 Of 14supporting
confidence: 82%
“…The antioxidant activity of C. papaya might be mediated through various systems, for example, metal chelation, hydroxyl radical destruction and impact cellular repair catalysts or reaction with peroxyl radicals (Sagnia et al, ). The findings of the present GC‐MS analysis of CPE revealed the prevalence of oleic acid and eugenol that have antioxidant properties (Elagbar, Naik, Shakya, & Bardaweel, ; Mamadalieva, Sharopov, Satyal, Azimova, & Wink, ). Eugenol act by preventing the free radical formation, remove radicals before damage can occur, repair oxidative damage and eliminate damaged molecules (Ali et al, ).…”
Section: Discussionmentioning
confidence: 71%
“…The flavonoids of this species have been well studied [ 32 ]. Constituents of the essential oil of the aerial parts of S. immaculata growing in Uzbekistan were reported as including acetophenone (30.39%), eugenol (20.61%), thymol (10.04%), linalool (6.92%), 1-octen-3-ol (2.89%), 4-vinylguaicol (2.50%), and 1,8-cineol (2.25%) ( Table 1 ) [ 33 ].…”
Section: Essential Oils From the Uzbek Lamiaceae Speciesmentioning
confidence: 99%
“…The chloroform extract of S. ramosissima showed potent cytotoxic effects to Trypanosoma brucei TC221, and HeLa, HepG-2, and MCF-7 cancer cells [ 32 ]. The essential oils from S. ramosissima showed that germacrene D (23.96%), β-caryophyllene (11.09%), linalool (9.63%), hexadecanoic acid (8.34%), caryophyllene oxide (5.90%), eugenol (5.29%), acetophenone (4.67%), thymol (3.01%), and 4-vinylguaicol (2.42%), were the principal components ( Table 1 ) [ 33 ].…”
Section: Essential Oils From the Uzbek Lamiaceae Speciesmentioning
confidence: 99%
See 1 more Smart Citation